2020
DOI: 10.3758/s13428-020-01407-2
|View full text |Cite
|
Sign up to set email alerts
|

t-Test and ANOVA for data with ceiling and/or floor effects

Abstract: Ceiling and floor effects are often observed in social and behavioral science. The current study examines ceiling/floor effects in the context of the t-test and ANOVA, two frequently used statistical methods in experimental studies. Our literature review indicated that most researchers treated ceiling or floor data as if these data were true values, and that some researchers used statistical methods such as discarding ceiling or floor data in conducting the t-test and ANOVA. The current study evaluates the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 30 publications
2
45
1
4
Order By: Relevance
“…The coefficient of determination (R 2 ) describes the variation on the dependent variable. R 2 values (Gouda & El-Hoshy, 2020;Jain et al, 2021) indicated the limitations of the dependent variable (Liu & Wang, 2021;Outram et al, 2021). The value ~ one  independent variables provide all information on the dependent variable prediction (Liu & Wang, 2021;Taylor et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The coefficient of determination (R 2 ) describes the variation on the dependent variable. R 2 values (Gouda & El-Hoshy, 2020;Jain et al, 2021) indicated the limitations of the dependent variable (Liu & Wang, 2021;Outram et al, 2021). The value ~ one  independent variables provide all information on the dependent variable prediction (Liu & Wang, 2021;Taylor et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The profitability affected capital structure (Chen, Xu, & Yang, 2021;Liu & Wang, 2021;Outram, Couperthwaite, Martens, & Millar, 2021). This capital structure is very important.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Tabla del diseño experimentalPosteriormente se realizará el análisis de varianza ANOVA[10] para poder conocer si sus resultados son de significancia estadística. Tabla 4 muetra los resultados experimentalmentes para el PVC .…”
unclassified